RE-EXISTENCE OF ASTRONOMY BY THE ARCHIPELAGO SCHOLAR - Hosen Hosen (Al-Hilal: Journal of Islamic Astronomy, 2020)
Abstract The science of Islamic astronomy that develops in the Indonesian archipelago is quite diverse with various methods of approach and defined criteria. Along with the development of science and technology, the works of Indonesian archipelago mufti on science of Islamic astronomy seemed to have sunk without a trace. There are only a few that still exist and can be enjoyed by researchers and observers of science of Islamic astronomy. The rest has not been touched to be developed, let alone to be reconstructed. Reconstruction and reexamination of the science of Islamic astronomy by the previous mufti of Indonesian archipelago is very important for several things. As an appreciation for the services of the author, preserve and develope the scientific treasures. The writer examines this issue with the library research method. First, the writer traces the works of Indonesian mufti in an organized manner in each region. Second, classify these works according to the criteria of taqribī or taḥqīqī. Third, reconstruct the works that belong to the taqribī category into the taḥqīqī category. And fourthly, rewrite the works referred to as a form of preservation of scientific treasures in the field of Islamic astronomy. The results that will be obtained from the four stages above are, first; knowing how many previous works of Mufti of Indonesian archipelago in the field of Islamic astronomy in each region shows that Mufti of Indonesian archipelago  had a high concern over  the development of islamci astronomy at that time. Second; You will find a comparison of the number of works that belong to the taqribī and taḥqīqī categories. Third; By reconstructing the works of the taqribī category into the taḥqīqī category, it will further foster enthusiasm for carrying out scientific studies which are verybenefical in order to increase knowledge of Islamic astronomy. And fourth; The preservation of the scientific treasures of the Indonesian archipelago created by previous scholars of the Indonesian archipelago which can be used as a reference for future research.Keyword: archipelago scholar, islamic astronomy, reconstructionAbstrakIlmu falak yang berkembang di nusantara cukup beragam dengan berbagai metode pendekatan dan kriteria. Seiring dengan perkembangan ilmu pengetahuan dan teknologi, karya-karya ulama nusantara tentang ilmu falak seakan tenggelam tanpa bekas. Hanya ada beberapa yang masih eksis dan dapat dinikmati oleh para peneliti dan pemerhati ilmu falak. Selebihnya belum tersentuh untuk dikembangkan apalagi direkonstruksi. Rekonstruksi dan penelahaan kembali terhadap ilmu falak karya ulama nusantara terdahulu sangat penting dilakukan untuk beberapa hal. Sebagai penghargaan atas jasa para mu’allif, melestarikan dan mengembangkan warisan khazanah keilmuan. Penulis mengkaji hal ini dengan metode library research. Pertama penulis menelusuri karya-karya ulama nusantara secara terorganisir dimasing-masing daerah. Kedua melakukan klasifikasi karya-karya tersebut sesuai dengan kriteria taqribī atau taḥqīqī. Ketiga merekonstruksi karya yang masuk kategori taqribī menjadi kategori taḥqīqī. Dan keempat menulis kembali karya-karya dimaksud sebagai bentuk pelestarian khazanah keilmuan dibidang ilmu falak. Hasil yang akan diperoleh dalam melakukan empat tahapan diatas adalah, pertama; mengetahui seberapa banyak karya-karya terdahulu ulama nusantara dalam bidang ilmu falak di masing-masing daerah yang menunjukkan bahwa ulama nusantara memiliki perhatian yang tinggi terhadap berkembangnya ilmu falak pada saat itu. Kedua; akan ditemukan perbandingan jumlah dari karya tersebut yang termasuk kategori taqribī dan taḥqīqī. Ketiga; dengan merekonstruksi karya kategori taqribī menjadi kategori taḥqīqī semakin menumbuhkan semangat untuk melakukan kajian-kajian keilmuan falak yang sangat bermanfaat dalam rangka meningkatkan pengetahuan. Dan keempat; lestarinya khzanah keilmuan falak hasil karya ulama nusantara terdahulu yang dapat dijadikan rujukan untuk penelitian-penelitian di masa yang akan datang.Kata kunci: ulama nusantara, ilmu falak, rekonstruksi